Stress evolution of fault-and-thrust belts in 2D numerical mechanical models - Lee, Fang-Yi; Tan, Eh; Chang, Emmy T. (Frontiers in Earth Science, 2024)
We employed numerical models to examine the dynamics of fold-and-thrust belts (FTBs), particularly focusing on the spatial and temporal interplay between stress variations and fault development. Our study explores the effects of variables such as layer thickness, basal friction, and surface diffusivity on the FTBs’ structural development, emphasizing the conditions under which frontal thrusts form. We found that fault activities within FTBs exhibit a cyclic behavior characterized by phases of initiation, quiescence, and reactivation. For over 95% of the total cycle duration, the frontal thrusts are the only active structures, and the stress within the FTB predominantly remains in a critical state. During the remaining 5%, the stress becomes over-critical, leading to the formation of a proto-thrust zone and the reactivation of pre-existing thrusts within the FTB. The lateral growth rate of FTBs is directly related to the thickness of the deforming layer, with the progression of the deformation front maintaining a steady pace across the study period. Additionally, our analysis on the progression of FTBs highlights the critical role of zonal failure spacing in determining the structural styles within FTBs. Our results indicate that narrowly spaced zonal failures, which promote the emergence of low-angle forethrusts, are more likely to occur at increased distances from the backstop. This explains the sequential frontal failure in the FTB; however, the stress accumulating at the rear weak zones also play an important role in the evolutionary patterns of the FTB. Our study offers new insights into the complex processes governing the mountain formation.